Senescence in Vascular Smooth Muscle Cells and Atherosclerosis - Zha, Yiwen; Zhuang, Wenwen; Yang, Yongqi; Zhou, Yue; Li, Hongliang; Liang, Jingyan (Frontiers in Cardiovascular Medicine, 2022)
Vascular smooth muscle cells (VSMCs) are the primary cell type involved in the atherosclerosis process; senescent VSMCs are observed in both aged vessels and atherosclerotic plaques. Factors associated with the atherosclerotic process, including oxidative stress, inflammation, and calcium-regulating factors, are closely linked to senescence in VSMCs. A number of experimental studies using traditional cellular aging markers have suggested that anti-aging biochemical agents could be used to treat atherosclerosis. However, doubt has recently been cast on such potential due to the increasingly apparent complexity of VSMCs status and an incomplete understanding of the role that these cells play in the atherosclerosis process, as well as a lack of specific or spectrum-limited cellular aging markers. The utility of anti-aging drugs in atherosclerosis treatment should be reevaluated. Promotion of a healthy lifestyle, exploring in depth the characteristics of each cell type associated with atherosclerosis, including VSMCs, and development of targeted drug delivery systems will ensure efficacy whilst evaluation of the safety and tolerability of drug use should be key aims of future anti-atherosclerosis research. This review summarizes the characteristics of VSMC senescence during the atherosclerosis process, the factors regulating this process, as well as an overview of progress towards the development and application of anti-aging drugs.